Changing an engineering curriculum through a co-construction process: A case study - Neto, Octavio Mattasoglio (2019)
The objective of this work is to present a co-construction process of an Engineering curriculum, which used different active learning approaches to motivate students by addressing realistic problems faced by engineers, right from the beginning of the program. Idealized by the rectory of the institution, in a top-down decision, the new curriculum established certain guidelines for these new approaches. In a bottom-up contribution to the curriculum, teachers had to devise, implement and conduct activities. At an early stage, these activities were classified into three types: Projects, Engineering Practices, and Workshops. To analyze the implementation of this new curriculum, a qualitative approach was used during and data were collected through interviews, focus groups, and questionnaires. The results indicate that teachers who devised the activities played an important role in determining several aspects aimed at formalizing the new curriculum in a co-construction process, increasing the accuracy of the ideas presented in the idealization phase. Despite the benefits of these experiences, the results suggest that the potential of the new curriculum was not entirely fulfilled at this initial phase, particularly regarding the development of soft skills. Therefore, adjustments are needed to take full advantage of the changes.